Silver-PVP-nickel and ZnS layered surface plasmon resonance sensor for petrochemical sensing applications - Ansari, Gufranullah; Pal, Amrindra; Sharma, Kanupriya; Srivastava, Alok K.; Verma, Gaurav (Journal of materials research, 2025)
This work describes a new multilayered design for a chemical sensor that uses surface plasmon resonance (SPR) phenomena. The proposed design includes a layered arrangement with a PVP layer interfaced between a bi-metallic layer (Ag and Nickel metal layer) and an additional layer of ZnS. The sensing layer, with the target analyte (samples of petrol and diesel), is placed on top of this composite structure. The angle interrogation approach has been used for thorough analysis using an SF11 prism in the Kretschmann configuration for SPR excitation. Our findings show a significant increase in sensitivity when compared to conventional SPR sensors. The maximum sensitivity of 252.5 deg/RIU and maximum FoM of 113.75 RIU −1 for the current study has been obtained. This study represents a substantial improvement in SPR-based sensing technology, demonstrating the possibility of very sensitive and selective petrochemical detection applications. Graphical Abstract This work describes a new multilayered design for a chemical sensor that uses surface plasmon resonance (SPR) phenomena. The proposed design includes a layered arrangement with a PVP layer interfaced between a bi-metallic layer (Ag and Nickel metal layer) and an additional layer of ZnS. The sensing layer, with the target analyte (samples of petrol and diesel), is placed on top of this composite structure. The angle interrogation approach has been used for thorough analysis using an SF11 prism in the Kretschmann configuration for SPR excitation. Our findings show a significant increase in sensitivity when compared to conventional SPR sensors. The maximum sensitivity of 252.5 °/RIU and maximum FoM of 113.75 RIU -1 for the current study has been obtained. This study represents a substantial improvement in SPR-based sensing technology, demonstrating the possibility of very sensitive and selective petrochemical detection applications.